2014
DOI: 10.1177/0022034514527617
|View full text |Cite
|
Sign up to set email alerts
|

A miRNA-binding-site SNP of MSX1 is Associated with NSOC Susceptibility

Abstract: MSX1 is a favorable candidate gene for susceptibility to non-syndromic orofacial clefts (NSOCs). However, the roles of MSX1 genetic variants in the development of NSOC are controversial and vary among human populations. In the present study, the roles of 4 potentially functional single-nucleotide polymorphisms (SNPs) of MSX1 (rs12532 in 3'-untranslated region [UTR], and rs3821947, rs3821949, and rs4464513 in 5' upstream) were investigated in a case-control study of 602 NSOC cases and 605 healthy controls. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 29 publications
2
26
0
2
Order By: Relevance
“…Moreover, 3′‐UTR SNPs can induce disease pathogenesis through miRNA‐mRNA interaction . For example, Ma L et al demonstrated that SNP rs12532 within the 3′‐UTR of MSX1, to which miR‐3649 binds, is associated with NSOC susceptibility . ENCODE data indicate that SNP rs7552 alters the regulatory motifs of TBX5 (regulation of developmental processes; 12q24) and BRCA1 (DNA repair associated; 17q21) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 3′‐UTR SNPs can induce disease pathogenesis through miRNA‐mRNA interaction . For example, Ma L et al demonstrated that SNP rs12532 within the 3′‐UTR of MSX1, to which miR‐3649 binds, is associated with NSOC susceptibility . ENCODE data indicate that SNP rs7552 alters the regulatory motifs of TBX5 (regulation of developmental processes; 12q24) and BRCA1 (DNA repair associated; 17q21) .…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have given an illustration of the differential expression of tissue miRNAs in murine upper lip [8], specific role of miRNAs in mouse embryos craniofacial morphogenesis [7,23]. Additionally, SNPs in the miRNA-binding sites were reported to be associated with non-syndromic orofacial clefts susceptibility [24]. Since miRNAs could regulate 30% of proteincoding genes through posttranscriptional silencing in mammals, the dysregulation of miRNAs in NSCL patients could make a profound influence on various biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Figure outlines the study selection process in a flowchart following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta‐Analyses) guidelines (Table ). A total of 142 citations during the initial search were followed by a series of omissions (S1 List A) that eventually yielded 15 articles for inclusion in the meta‐analysis (Cardoso et al, ; Gurramkonda, Syed, Murthy, & Lakkakula, ; Hong et al, ; Huang et al, ; Ibarra‐Arce et al, ; Jagomagi et al, ; Ma et al, ; Mostowska et al, ; Park et al, ; Rafighdoost et al, ; Seo, Park, Kim, & Baek, ; Song et al, ; Sun et al, ; Tongkobpetch, Siriwan, & Shotelersuk, ; Velazquez‐Aragon et al, ).…”
Section: Resultsmentioning
confidence: 99%